La résilience organisationnelle comme outil de relance d’une destination. Le cas du Québec - Khomsi Mohamed Reda (Études Caribéennes)
The concept of resilience has been strongly mobilized over the past two decades to understand and analyze how organizations develop coping, or recovery, strategies after disruptive events. That said, and given the increasingly complex environment in which organizations operate, researchers suggest that organizations adopt a culture of organizational resilience in place of resilience policies in an effort to continually adapt to changing environments. At the level of tourist destinations, seen as an ecosystem whose performance depends on the degree of collaboration between the actors that make them up, the adoption of an organizational resilience approach involves challenging traditional governance models. As such, this article attempts to explain how the province of Quebec (Canada) has succeeded in reviving its tourism sector through a review of its governance within a new structure that requires close collaboration between the public and private sectors.